A Time Series Analysis of Vegetation Succession on Lava Flow Fields at Hekla Volcano: Assessing the Utility of Landsat Data - Alexander Thomas Merrington 1993- (2019)
With the advent of space-borne scientific platforms such as the Landsat satellites, utilising remote sensing for monitoring vegetation dynamics is commonplace in research. However, studies that focus on vegetation succession on lava flow fields are much rarer. This study uses remote sensing to monitor vegetation succession on Icelandic lava flows. The aim was to evaluate whether vegetation succession can be monitored on Hekla volcano’s lava flows via available Landsat data, and if so, assess the succession in space. The literature presented focuses on the Icelandic landscape, vegetation succession on lava flows and remote sensing of vegetation. NDVI images were used to construct time series of vegetation growth on prime Icelandic lava flows and change detection was achieved via image differencing. These series indicated vegetation growth on all lava flows analysed. The impact of elevation can be inferred as having a negative relationship to succession, though the relationship was weak, especially for older (pre 1970) lava flows which already have established vegetation. Change detection maps indicated that lava flows act as a stable substrate for vegetation growth in this erosion prone landscape. Initial stage vegetation succession was visible within a 10-15 year time frame after lava flow emplacement. The application of the methods used are considered successful and are capable of being applied to other regions in Iceland for further study and refinement of the information needed to monitor the spatial dimension of early vegetation succession stages. However, more knowledge of Icelandic phenology and better treatment of errors in the images are needed in future studies. Með komu vísindalegra vettvanga úr geimnum eins og Landsat gervihnattatungla og notkun þeirra til fjarkönnunar (e. remote sensing)er alegeng aðferð til rannsókna við eftirlit með gróðurvirkni. Hinsvegar, eru rannsóknir sem einblína á framfarir í gróðri í hraunbreiðum með aðferð fjarkönnunar óalgengar. Þessi rannsókn notast við fjarkönnun til ...